COMPLICATION AND SAFETY OF TRANSPERINEAL PROSTATE BIOPSY USING NOVEL AFFORDABLE VY PROBE (TPPB-VY) IN CLINICAL PRACTICE : A PILOT STUDY - Ali Ridho Al Haddar; Pramod, Sawkar Vijay; Ferry Safriadi (Indonesian Journal of Urology, 2023)
Objective: This study was aimed to know the complication and safety of TPPB-VY in clinical practice. Material & Methods: TPPB were performed in 34 patients between January 2019 and Juni 2021. Ethical approval of this study was sought from the hospital authorities (IRB number: LB.02.01/X.6.5/ 55/2020). Patients underwent systematic 10-12 core TPPB depend on the prostate volume with intravenous light sedation. The patient was included to the study if PSA ≥ 4 ng/ml and/or Digital Rectal Examination (DRE) results suggestive of prostate cancer. Procedures were performed without any antibiotic prophylaxis or an enema before the procedure and post procedure the patients just get an oral fluoroquinolones and low potent analgetics (if needed). The complication include pain level post procedure (using VAS), perineal hematoma, fever and retention post biopsy were recorded. Results: In all, 34 patients were included in the study. The result showed that perineal pain perceived by patients post procedure were 76.47% (26 out of 34 patients) but the VAS score just mild around 0-2. There were 23.53% (8 out of 34 patients) hematuria, 5.88% (2 out of 34 patients) acute urinary retention and 2.9 % (1 out of 34 patients) perineal hematoma. No fever or clinical infection was observed and 82.35% (28 out of 34 patients) patients presented with minor complications (ClavienDindo I). Only one of the patients were hospitalized due to the post-biopsy complication that need intervention. Conclusion: This is the first study TPPB using Novel Affordable VY probe. The results show clinically insignificant complication without infection. TPPB using Novel Affordable VY probe is feasible and safe.